2016
DOI: 10.3352/jeehp.2016.13.30
|View full text |Cite
|
Sign up to set email alerts
|

The applicability of a validated team-based learning student assessment instrument to assess United Kingdom pharmacy students’ attitude toward team-based learning

Abstract: PurposeIt aimed at testing the validity and reliability of a validated team-based learning student assessment instrument (TBL-SAI) to assess United Kingdom pharmacy students’ attitude toward TBL.MethodsTBL-SAI, consisting of 33 items, was administered to undergraduate pharmacy students from two schools of pharmacy each at University of Wolverhampton and University of Bradford were conducted on the data, along with comparison between the two schools.ResultsStudents’ response rate was 80.0% (138/173) in completi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
27
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 5 publications
5
27
1
Order By: Relevance
“…Kaiser-Meyer-Olkin test (KMO) was performed for the whole instrument items for measuring sampling adequacy. Values higher than 0.60 for the total items indicate that factor analysis can be conducted [13]. A principal component analysis with varimax rotation was conducted on each subscale of TBL-SAI to identify the underlying factor structure.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Kaiser-Meyer-Olkin test (KMO) was performed for the whole instrument items for measuring sampling adequacy. Values higher than 0.60 for the total items indicate that factor analysis can be conducted [13]. A principal component analysis with varimax rotation was conducted on each subscale of TBL-SAI to identify the underlying factor structure.…”
Section: Discussionmentioning
confidence: 99%
“…The TBL-SAI scale originally developed for assessing TBL in baccalaureate nursing students [15] and was found to be reliable among medical students [4,16] and other health profession students [13,14]. The psychometric properties of the TBL-SAI scale have been reported as satisfactory, and the construct validity of the scale has been examined previously elsewhere [13,15]. The instrument is a self-administrated contains 33 items (with total scores ranging from 33-165) designed to measure students' attitude toward TBL.…”
Section: Instrument Descriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using a locally generated measure, in a recent study of pharmacy students experiencing TBL, researchers found that students (n=53) significantly preferred TBL to traditional lecture (Frame et al, 2015). In another unrelated study of pharmacy students (n=201), using the TBL-SAI as the measurement instrument, researchers reported a mean score of 33.0 on the TBL-SAI satisfaction subscale (Nation, Tweddell, & Rutter, 2016). This score is 5 points, or 18%, higher than the satisfaction subscale neutral score of 28.0 (Mennenga, 2012).…”
Section: Discussionmentioning
confidence: 99%